Pengaruh Pelatihan Kerja, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Morich Indo Fashion Kabupaten Semarang - Wildan Muharram; Robby Andika Kusumajaya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the influence of job training, work motivation, and work discipline on employee performance at PT. Morich Indo Fashion, Semarang Regency. Data was collected using a 5-point Likert scale questionnaire from 90 employees selected through purposive sampling. Data analysis was performed using multiple linear regression and hypothesis testing (t-test and F-test) with SPSS version 25 software. The results reveal that partially, the three independent variables job training (β=0.230; p=0.017), work motivation (β=0.309; p=0.001), and work discipline (β=0.410; p=0.000) have a positive and significant effect on employee performance. Simultaneously, these three variables also have a significant combined effect (F=188.489; p=0.000), with a coefficient of determination of 86.3%. These findings confirm that improvements in training, motivation, and discipline collectively explain a large portion of the variation in enhancing employee performance in the garment manufacturing company. This study recommends that the company focus its resources more on developing sustainable training programs, effective motivational systems, and consistent enforcement of work discipline to optimize human resource performance.